Parental Communication Increases Student Learning Motivation in Elementary Schools - Amin, Alfauzan; Alimni, Alimni; Kurniawan, Dwi Agus; Azzahra, Miftahul Zannah; Septi, Sabila Eka (Universitas Pendidikan Ganesha, 2021)
There is still a lack of parental communication on students' learning motivation at the elementary school level. It has an impact on the level of student learning motivation that is less. This study aims to analyze parental communication on students' learning motivation in the learning process of Islamic religious education. This type of research is a mixed-method, namely quantitative and qualitative with an explanatory design. The subjects in this study were parents and elementary students. Data collection techniques used in this study were the distribution of questionnaires and interviews. The data analysis method used is a quantitative descriptive analysis by testing the findings using apps, record results, and concluding. Quantitative description by distributing questionnaires and conducting interviews. The results showed differences and influences between parental communication and student learning motivation in Islamic religious education subjects. So, it can be concluded that parental communication on student learning motivation has been carried out very well, although not optimally. Parental communication has been done well so that students' learning motivation will also increase and impact increasing student learning discipline.